Cluster-based industrialization in China: Financing and performance - Long, Cheryl; Zhang, Xiaobo (International Food Policy Research Institute, 2009)
Using firm-level data from China's two recent censuses (Industry Census 1995 and Economic Census 2004) and a new measure of clustering (industry proximity), we show that China's rapid industrialization is marked by increased clustering. A higher degree of clustering is further shown to be associated with greater export growth and higher total factor productivity. We also find supporting evidence that clustering helps ease the credit constraints facing many small and medium enterprises through two mechanisms: (1) within a cluster, finer division of labor lowers the capital barriers to entry and (2) closer proximity makes the provision of trade credit among firms easier. Since both mechanisms reduce the need for external financing, a larger number of firms=and thus greater competition-emerge within clusters, which helps explain the higher levels of exports and total factor productivity. This cluster-based industrialization model fit particularly well with China's comparative advantage during its initial stage of takeoff, which was marked by scarcity of capital and an inefficient financial system. Hence our findings may be helpful to other developing countries with similar factor endowment patterns that are considering cluster-based development strategies.